Governmental Banking Finance and its Impact on GDP (Gross domestic product) and Household Expenditure in Iraq for the Period from (2004-2017) - Abdulhasan, Safa Rabeeh (International Journal of Psychosocial Rehabilitation, 2020)
Iraqi banking sector witnessed many reforms after 2003, like issuing several laws, including regulating the work of monetary policy such as Law No. 56 of 2004, that allowed the independency for Central Bank, after it was a tool to finance the deficit of government budget, as well as restoring confidence to the local currency and the fight against deflate. The commercial banking sector witnessed the issuance of Law No. 94 of 2004, which granted banks the freedom to expand their credit limits and left the setting of the creditor and debtor interest rates. Commercial banks began to expand the granting of domestic credit in light of the economic liberalization witnessed in Iraq. However, governmental commercial banks played the largest role in covering the market with the necessary financing, by the expansion of loans granting in all forms, through its seven banks (- Rafidain bank, Al-Rasheed Bank, the Trade Bank of Iraq and Alnahrain Islamic Bank and the three specialized banks). In light of the apparent decline of contribution of private commercial banks, so the subject of research discusses the role of commercial banks in stimulating economic growth, for the period 2004-2017, by the construction of standard models, using models of time lag (ARDL). Keywords—